Type 2 Diabetic Sepsis Patients Have a Lower Mortality Rate in Pioglitazone Use: A Nationwide 15-Year Propensity Score Matching Observational Study in Taiwan - Ming-Shun Hsieh; Sung-Yuan Hu; Shu-Hui Liao; Chia-Ming Chang; Vivian Chia-Rong Hsieh; Chorng-Kuang How (Emergency Medicine International)
Background. Pioglitazone use via the PPARγ agonist in sepsis patients is inconclusive. It was based on a great number of animal studies. However, except for information from animal studies, there are merely any data of human studies for reference. Methods. This study was conducted by a unique database including 1.6 million diabetic patients. From 1999 to 2013, a total of 145,327 type 2 diabetic patients, first admitted for sepsis, were enrolled. Propensity score matching was conducted in a 1 : 5 ratio between pioglitazone users and nonusers. Multivariate logistic regression was conducted to evaluate the adjusted odds ratios (aORs) of hospital mortality in pioglitazone users. Further stratification analysis was done and Kaplan–Meier plot was used. Results. A total of 9,310 sepsis pioglitazone users (defined as “ever” use of pioglitazone in any dose within 3 months prior to the first admission for sepsis) and 46,550 matched nonusers were retrieved, respectively. In the multivariate logistic regression model, the cohort of pioglitazone users (9,310) had a decreased aOR of 0.95 (95% CI, 0.89–1.02) of sepsis mortality. Further stratification analysis demonstrated that “chronic pioglitazone users” (defined as “at least” 4-week drug use within 3 months) (3,399) were more associated with significant aOR of 0.80 (95% CI, 0.72–0.89) in reducing sepsis mortality. Conclusions. This first human cohort study demonstrated the potential protective effect of chronic pioglitazone use in type 2 diabetic sepsis patients.